The influence of local brand image and product quality on customer loyalty at PT. Sinar Menara Deli Medan - Ronnie MT Sirait (JURNAL GLOBAL MANAJEMEN, 2021)
In managing a leading company, it is necessary to pay attention to the level of Local Brand Image and Product Quality as one of the elements that influence the Purchasing Decision. This study aims to determine the effect of local brand image and product quality on purchasing decisions simultaneously. The type of research used is explanatory research with a quantitative approach. The number of samples used in this study were 66 respondents, namely a number of customers at PT. Graha Aluminum Products. The analysis technique used is multiple linear regression analysis with hypothesis testing, namely F test (simultaneous) and T test (persial). The result of multiple linear regression Y = 3,326 + 0,357X1 + 0,695X2, shows that the local brand image variable has a significant effect on purchasing decisions with a value of tcount 3.105> ttable 2.026. Product Quality variable shows the tcount value of 3.105> 2.026, this means that Product Quality has a significant effect on Purchasing Decisions. The result of Fcount is 237.052> Ftable value of 3.25, that there is a significant influence between the variables of Local Brand Image and Product Quality simultaneously affect the Purchase Decision. While the value of the coefficient of determination, it is known that the Adjusted R Square obtained is 0.924 (92.4%), which means that the Local Brand Image and Product Quality are able to explain the Purchase Decision which illustrates the influence of other variables for the Purchasing Decision of PT. Graha Aluminum Products. Advice given to the leadership of PT. Graha Aluminum Medan Products to further enhance the Local Brand Image and Product Quality so that Purchase Decisions are higher.